Intersectionality Analysis of the Impact of Anti-Female Genital Mutilation/Cutting Policies in Indonesia and Egypt - Gustina, Nadiah Atsil; Nareswari, Laras Ayu (Jurnal Politik, 2023)
Indonesia and Egypt are the two countries with the highest prevalence rates of Female Genital Mutilation / Cutting (FGM/C) in the world. Several policies have been issued in order to reduce the number of cases of female circumcision, but they have not shown significant results. Therefore, the authors want to explain why the implementation of the anti-FGM/C policy has not succeeded in reducing the number of female circumcisions in Indonesia and Egypt. The authors argue that the leading cause of these problems is that the anti-FGM/C policies in both countries neglect the socio-cultural aspects of society, and both countries share cultural similarities in how they view women. Circumcision is not only seen as a way to purify or glorify women but is also seen as a repressive measure to limit the freedom and rights of women's bodily autonomy. In addition, a decisive view of religion also influences the high demand for female circumcision. This condition provides different experiences for women in the two countries than other countries implementing anti-FGM/C policies. The position of women in Indonesia and Egypt who are still bound by cultural and religious values makes them more vulnerable to experiencing female circumcision because they do not have the choice of women in other regions.